High performance structure materials : selected, peer reviewed papers from the Chinese Materials Congress 2012 (CMC 2012), July 13-18, 2012, Taiyuan, China - Chinese Materials Congress (2012 : Taiyuan, China); Han, Yafang; Lin, Junpin; Xiao, Chengbo, editor; Zeng, Xiaoqin, editor (Durnten-Zurich, Switzerland : Trans Tech Publications, 2013)
The collection of peer reviewed papers C-MRS 2012 meeting includes 146 papers selected from Symposium O: TiAl alloys and advanced structure intermetallics, Symposium Q: Aerospace materials, Symposium R: Advanced Magnesium alloy and application, Symposium S: Superalloys, and Symposium T: Advanced titanium alloys.